The effect of UV exposure and heat treatment on crystallization behavior of photosensitive glasses - Kibrisli, Orhan; Ersundu, Ali Ercin (SPRINGER, 2018)
In this study, photosensitive glasses in the Na2O-ZnO-Al2O3-SiO2 system with photosensitizing agents (cerium, silver, tin, antimony) and halogenides (NaF and KBr) were synthesized through a conventional melt-quenching technique. The crystallization mechanism was investigated for solely heat-treated and UV-exposed + heat-treated samples using differential thermal analysis (DTA), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS) and scanning electron microscopy (SEM) techniques to understand the effect of UV exposure on crystallization behavior of photosensitive glasses. Accordingly, non-isothermal DTA measurements were performed at different heating rates to determine crystallization peak, T-p, and onset, T-c, temperatures. For solely heat-treated samples, the kinetic parameters such as the Avrami constant, n, and morphology index, m, were calculated as 1 from the Ozawa method indicating surface crystallization and the value of crystallization activation energy was calculated as 944 kJ/mol using modified Kissinger method. On the contrary, bulk crystallization was found to be predominant for UV exposed + heat-treated samples revealing that UV exposure is the primary cause of bulk crystallization in photosensitive glasses.
Keywords: THERMO-REFRACTIVE GLASS; PHOTOTHERMOREFRACTIVE GLASS; KINETICS; GROWTH; Materials Science; Physics